1998
DOI: 10.1086/516355
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance and Outcome of Anaerobic Bacteremia

Abstract: We retrospectively studied the incidence of anaerobic bacteremia during 6 years (1991-1996) at Turku University Central Hospital (Turku, Finland). The clinical significance of a positive anaerobic blood culture, the effect of a positive culture on the choice of antimicrobial therapy, and the outcome for patients were evaluated. Cultures of blood from 81 patients yielded anaerobic bacteria (4% of all bacteremias). Anaerobic bacteremia was clinically significant in 57 patients (0.18 cases per 1,000 admissions). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
75
0
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 15 publications
8
75
0
5
Order By: Relevance
“…Anaerobic bloodstream infection episodes were also more likely to be associated with hypothermia and hypotension at the time the blood culture was obtained. Anaerobic bacteremia has been associated in other recent studies with crude mortality rates of 25 to 38% (10,13,22). Given that anaerobes accounted for only 3% of bacteremias in our study, a finding similar to those of other recent reports (13,22), it is interesting that it was the organism group with the strongest independent association with mortality.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Anaerobic bloodstream infection episodes were also more likely to be associated with hypothermia and hypotension at the time the blood culture was obtained. Anaerobic bacteremia has been associated in other recent studies with crude mortality rates of 25 to 38% (10,13,22). Given that anaerobes accounted for only 3% of bacteremias in our study, a finding similar to those of other recent reports (13,22), it is interesting that it was the organism group with the strongest independent association with mortality.…”
Section: Discussionsupporting
confidence: 91%
“…Anaerobic bacteremia has been associated in other recent studies with crude mortality rates of 25 to 38% (10,13,22). Given that anaerobes accounted for only 3% of bacteremias in our study, a finding similar to those of other recent reports (13,22), it is interesting that it was the organism group with the strongest independent association with mortality. The low incidence of anaerobic bacteremia makes it more difficult to examine its independent impact on mortality in any but the largest of studies.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, blood sample was obtained before colonoscopy and it is suggested that these microorganisms were able to achieve bloodstream through tumor tissue and they may remain in state of bacteremia for long period [6]. In this case, the infection in rectal cancer involves disruption of the normal barrier due to tumor-induced ulceration, followed by bloodstream invasion, in accordance with Mirza [7] Bacteremia caused by anaerobic bacteria represents from 0.5% to 12% of the total of bacteremia, and the mortality is approximately between 25% and 44% [8]. Studies have shown that bacterial community in an individual is relatively stable along the distal digestive tract [9].…”
Section: Discussionmentioning
confidence: 91%
“…Others have advocated the selective use of anaerobic blood cultures, restricting them to patients with specific illnesses or diseases or undergoing specific procedures such as colorectal or gynecological surgery (1,2,8,9,12). Indeed, the topic of whether an anaerobic blood culture should routinely be performed was the subject of several articles and editorials in the medical literature (6,7,10). No expert in the field has suggested that the total amount of blood cultured be reduced by the elimination of an anaerobic blood culture bottle.…”
Section: Discussionmentioning
confidence: 99%